Redefining GERD management: The emerging role of potassium-competitive acid blockers - Vania Azalia Gunawan; Titong Sugihartono (Gülhane Tıp Dergisi, 2025)
Gastroesophageal reflux is the regurgitation of gastric contents into the esophagus, while gastroesophageal reflux disease (GERD) denotes symptoms or mucosal damage due to recurrent reflux, manifesting as heartburn, acid regurgitation, and dysphagia. GERD’s prevalence is lower in Asia (6-7%) than in Western countries (15-21%). Although not inherently dangerous, GERD can significantly reduce quality of life and cause complications, such as esophageal stricture and Barrett’s esophagus. Proton pump inhibitors (PPIs) are the primary pharmacologic therapy, but approximately 40% of patients remain symptomatic. Long-term PPI use raises concerns regarding bacterial colonization, nutrient absorption, and other side effects. Potassium-competitive acid blockers emerge as a promising alternative that provides stronger acid suppression with potential benefits in refractory GERD cases and safety concerns associated with prolonged PPI use.